Electrochemical‐Conditioning‐Free and Water‐Resistant Hybrid AlCl3/MgCl2/Mg(TFSI)2 Electrolytes for Rechargeable Magnesium Batteries. Issue 23 (7th February 2019) - He, Yishi; Li, Qi; Yang, Lanlan; Yang, Chaoran; Xu, Dongsheng
Abstract: Rechargeable magnesium batteries are a promising alternative to Li‐based energy storage because of their abundant and inexpensive components. The high sensitivity and reactivity of the organic Mg 2+ electrolyte makes their development challenging. Herein, we develop a new hybrid electrolyte, based on three simple inorganic salts of MgCl2, AlCl3, and Mg(TFSI)2 . The electrolyte exhibits unprecedented electrochemical performance for reversible deposition and stripping of Mg, with Coulombic efficiency up to 97 %, overpotential down to 0.10 V, good stability especially for aluminum and stainless‐steel current collectors. It maintained its activity even after introducing 2000 ppm water and it could be prepared from impure chemicals. A full cell with the hybrid electrolyte and Mg foil as anode, Mo6 S8 as cathode gave a specific capacity of 98 mAh g −1 and maintained 94 % capacity after 100 cycles at a rate of 0.20 C, indicating the good compatibility of the hybrid electrolyte. Abstract : A hybrid electrolyte consisting of AlCl3 /MgCl2 /Mg(TFSI)2 in THF was developed for rechargeable Mg batteries (TFSI=bis(trifluoromethanesulfonyl)imide, THF=tetrahydrofuran). It requires no conditioning, is water‐resistant, and shows excellent electrochemical performance in the reversible deposition and stripping of magnesium.